2016
DOI: 10.1155/2016/6267879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Specialized Yoga Program for Persons Admitted to a Complex Continuing Care Hospital: A Pilot Study

Abstract: Introduction. The purpose of this study was to evaluate a specialized yoga intervention for inpatients in a rehabilitation and complex continuing care hospital. Design. Single-cohort repeated measures design. Methods. Participants (N = 10) admitted to a rehabilitation and complex continuing care hospital were recruited to participate in a 50–60 min Hatha Yoga class (modified for wheelchair users/seated position) once a week for eight weeks, with assigned homework practice. Questionnaires on pain (pain, pain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 106 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…Individuals living with an implantable cardioverter defibrillator who were randomized to a once weekly 8-week yoga intervention demonstrated increased self-compassion at the end of the yoga program compared to a treatment-as-usual group 57. Improvements in self-compassion were also observed from preintervention to postintervention in a pilot research trial evaluating an 8-week yoga intervention for individuals with chronic complex disease and disability 52. Notably, self-compassion was found to mediate changes in anxiety from preintervention to postintervention, speaking to the mechanisms of yoga practice and philosophy didactics on psychological experience.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Individuals living with an implantable cardioverter defibrillator who were randomized to a once weekly 8-week yoga intervention demonstrated increased self-compassion at the end of the yoga program compared to a treatment-as-usual group 57. Improvements in self-compassion were also observed from preintervention to postintervention in a pilot research trial evaluating an 8-week yoga intervention for individuals with chronic complex disease and disability 52. Notably, self-compassion was found to mediate changes in anxiety from preintervention to postintervention, speaking to the mechanisms of yoga practice and philosophy didactics on psychological experience.…”
Section: Discussionmentioning
confidence: 93%
“… 57 Improvements in self-compassion were also observed from preintervention to postintervention in a pilot research trial evaluating an 8-week yoga intervention for individuals with chronic complex disease and disability. 52 Notably, self-compassion was found to mediate changes in anxiety from preintervention to postintervention, speaking to the mechanisms of yoga practice and philosophy didactics on psychological experience. The authors concluded that self-compassion may enable individuals to contact distressing inner experience without ascribing evaluative or judgmental meaning, to bypass ruminative tendencies, and to select healthful and agential actions to create positive change.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations